Highly flexible method for fabrication of poly (Glycidyl Methacrylate) grafted polyolefin nanofiber - Abbasi, A. (Elsevier Ltd, 2018)
This paper describes the development of highly flexible and simple approaches toward fabrication of syndiotactic polypropylene (s-PP) nanofibers of desired morphology and functionalization with modifiable poly (glycidyl methacrylate) (PGMA) of desired level. To this end, the nanofibers were fabricated by electrospinning. Optimization of electrospinning process was carried out using Box-Behnken design (BBD) of response surface method (RSM) and a linear mathematical model was developed to relate various electrospinning parameters to the average fiber diameter. According to the model calculation, a minimum fiber diameter of 336 nm was supposed to be obtained at a flow rate of 4 ml/min, applied voltage of 16 kV and needle tip to collector distance of 20 cm, which was confirmed by the experiment with only 2.2 error. Furthermore, prediction capability experiments of the model revealed maximum 5.3 and 8.9 deviation from the model-predicted values for applied high voltage and flow rate, respectively. Radiation induced grafting of glycidyl methacrylate (GMA) on the electrospun nanofibers was carried out to impart desired density of oxirane groups to the nanofibrous s-PP. Â© 2018 Elsevier Ltd